Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 2: 1731-1733 - Gottsched, Johann Christoph (Briefwechsel, 2015)
This second volume of the letter edition shows that Gottsched already occupied an influential position in the academic and cultural life of Leipzig in the early 1730s. This is documented by his university career and his work as a senior member of the German Society. The correspondence provides detailed insights into the work of this first society for the study of German language and literature and, in addition, illuminates new facets of the reception history of such central works as Critische Dichtkunst (1730).